2011
DOI: 10.1007/s10337-011-2090-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chlorantraniliprole Residues in Corn and Soil by UPLC–ESI–MS/MS and Its Application to a Pharmacokinetic Study

Abstract: A rapid, highly sensitive, and selective method was developed for the determination of the insecticide chlorantraniliprole (CAP) in corn and soil using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Samples were extracted with acetonitrile, and aliquots were cleaned with solid-phase extraction cartridges. Two precursor-product ion transitions for CAP were measured and evaluated to provide maximum confidence in the results. Average recovery for soil, corn grain, and corn straw at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…The insecticides tested achieved levels below the MRL of 0.05 mg/kg much faster than their PHIs (ScholzStarke et al 2017). Our results are in agreements with Dong et al who studied the determination of CAP residues in corn and soil by UPLC-ESI-MS/MS and they found that the half-life of CAP ranged from 12.6 to 23.1 days in soils and ranged from 4.9 to 5.4 days in corn (Dong et al 2011). Zhang and other calculated the half-life of CAP in soil of rice field ecosystem to be 16.0 days (Zhang et al 2012).…”
Section: Figure 3 Dissipation Curves Of Cap In Soil a And B With Or supporting
confidence: 93%
“…The insecticides tested achieved levels below the MRL of 0.05 mg/kg much faster than their PHIs (ScholzStarke et al 2017). Our results are in agreements with Dong et al who studied the determination of CAP residues in corn and soil by UPLC-ESI-MS/MS and they found that the half-life of CAP ranged from 12.6 to 23.1 days in soils and ranged from 4.9 to 5.4 days in corn (Dong et al 2011). Zhang and other calculated the half-life of CAP in soil of rice field ecosystem to be 16.0 days (Zhang et al 2012).…”
Section: Figure 3 Dissipation Curves Of Cap In Soil a And B With Or supporting
confidence: 93%
“…Acetamiprid has been reported to have a short half-lives in studies of zucchini (1.9 days) [16], chili peppers (2.24–4.84 days) [18], watermelon (3.1–3.9 days) [17], okra fruit (2.3 days) [37], green tea shoots (1.82–2.33 days) [38], and mustard plants (1.02 and 1.59 days) [39]. Previous studies have shown that chlorantraniliprole also tends to degrade rapidly with half-lives of 4.9–5.4 days in corn straw [40], 1.25 and 1.36 days in cauliflower [26], 2.7 days in grape [24], 3.3 days in tomato, and 0.93–1.33 days in berseem leaf. Overall, the dissipation tendencies of both pesticides in this study were slightly slower than those of previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…The present finding on DT 50 of chlorantraniliprole is differing from the results reported with DT 50 for cauliflower 1.25–1.36 days ( Kar et al., 2012 ), tomato 3.30 days ( Malhat et al., 2012 ) okra 1.60–1.70 days ( Vijayasree et al., 2015 ), brinjal 1.58–1.80 days ( Vijayasree et al., 2015 ), green chilli 1.58–1.80 days ( Ahlawat et al., 2019 ), 1.26 days ( Paramasivam, 2020 ). This variation might be the resultant of the prevailing environmental factors and processes viz., temperature, relative humidity, volatilization and photo-degradation at field conditions ( Dong et al., 2011 ; Kar et al., 2012 ; Zhang et al., 2012 ; Solanki et al., 2019 ; Paramasivam, 2020 ) which are not consistent in different geographical regions.…”
Section: Resultsmentioning
confidence: 82%